Cellular Stiffness Measurement for 3D Biological Printing - Wenna, Badjo (2016)
During 3D biological printing, cells can sense their environment and change their own properties accordingly. In order to understand how cells modulate their stiffness with resp ect to their environmental stiffness, micropipette aspiration method was used to measure the aspiration lengths of porcine mesenchymal stem cells (pMSCs), which were cultured on polydimethylsiloxane (PDMS) substrates with different stiffness for different time periods, under certain pressure. After the measurem ents, both elastic and viscoelastic models were used to analyze the elasticity of the cell. Clear relationship between PDMS stiffness and cell stiffness could not be obtained with elastic model. However, from viscoelastic model, it gives that cells cultured on softest PDMS had the largest elastic modulus while on stiffest PDMS had lowest elastic modulus.